Eradicating child maltreatment : evidence-based approaches to prevention and intervention across services - Bentovim, Arnon; Gray, Jenny (Social work consultant); Ward, Harriet, 1948- (Jessica Kingsley Publishers, 2015)
Is it possible to overcome the enduring problem of child maltreatment? In "Eradicating Child Maltreatment," leading international figures in the field of child welfare address this enduring and thorny question, setting out a public health approach to prevention. It draws on groundbreaking research and practice on prevention and early intervention from around the globe spanning health, social care, education and criminal justice. Contributors describe what is known about the incidence of child maltreatment, how far we have succeeded in eradicating it, which preventative strategies have been proven to be effective, and offers evidenced recommendations for policy and practice. Aiming to draw us nearer to the goal of a world free from child maltreatment first articulated by the visionary paediatrician Dr. C. Henry Kempe in 1978, this important book provides new insights for professionals, managers, academics, and policymakers across the range of child and family welfare services.